Designation of lectotypes for some Spanish and other western European Melitaea taxa, some with mixed syntypic series of M. phoebe ([Denis & Schiffermüller], 1775) and M. ornata Christoph, 1893 (Lepidoptera: Nymphalidae) - Russell, P. J. C.; Bartolozzi, L.; Hawkins, R. L.; Tennent, W. J.; Léger, T. (SHILAP Revista de lepidopterología, 2020)
Morphological characters of value in distinguishing Melitaea phoebe from M. ornata are exemplified from photographs of specimens from sympatric and partially synchronic populations in North Macedonia and Italy. Subspecies described as belonging to M. phoebe by several authors from specimens taken in Spain and other Western European countries are examined and their identities reviewed. Those which are shown to be subspecies of M. ornata are figured together with identification labels attached to the specimens. Where syntypes have been identified, lectotypes and paralectotypes are designated where appropriate. Some subspecies which are genuinely M. phoebe are commented upon. Eleven syntypes of M. phoebe occitanica are examined and found to comprise both M. phoebe and M. ornata; a phoebe lectotype is designated and its Type Locality is restricted to Barcelona, Spain. Lectotypes are also designated for the names bethunebakeri, ornatiformis, emipunica and punicata. Original identifications predate the separation of these two species and exemplify difficulties previous researchers had in separating them. M. ornata pseudornata is sunk in synomymy with M. ornata bethunebakeri. It is noted that some historic and often worn specimens are extremely difficult to identify with certainty.